A systematic review of self‐regulation strategies to improve academic outcomes of students with EBD. Issue 4 (31st January 2018) - Popham, Michelle; Counts, Jennifer; Ryan, Joseph B.; Katsiyannis, Antonis
Abstract : Self‐regulatory interventions have demonstrated numerous benefits for helping improve the academic performance of students. The purpose of this review was to report on the effectiveness and focus of academic self‐regulation interventions for children and adolescents with emotional and behavioural disorders. Thirty‐six studies published in 35 papers and involving 189 participants met inclusionary criteria. Overall, self‐regulation interventions showed moderate/medium effect size gains [percentage of nonoverlapping data (PND) 75%; standard mean difference (SMD) 2.27; Tau‐U 0.81] across academic subject areas. When assessing the effectiveness of self‐regulation interventions for addressing specific academic content areas, the largest ES gains were observed in reading (PND 93%; SMD 2.13; Tau‐U 0.94), although medium/moderate ES gains were observed in math (PND 71%; SMD 2.08; Tau‐U 0.70) and writing (PND 83%; SMD 2.57; Tau‐U 0.91). Self‐regulated strategy development, self‐monitoring interventions and strategy instruction were the predominant types of self‐regulation techniques implemented by researchers. There was evidence to support a claim of the generalisation and maintenance of findings. Implications, limitations and areas for future research are discussed.